The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3109/0886022x.2016.1172941
|View full text |Cite
|
Sign up to set email alerts
|

Medical ozone therapy reduces shock wave therapy-induced renal injury

Abstract: Objectives: Extracorporeal shock wave (ESW) lithotripsy is the preferred treatment modality for uncomplicated kidney stones. More recently free oxygen radical production following ESW application has been considered to be crucial in shock wave-induced renal damage. It has been shown that ozone therapy (OT) has ameliorative and preventive effects against various pathological conditions due to increased nitro-oxidative stress. In current study, we aimed to evaluate the efficacy of OT against ESW-induced renal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Overall it can be appreciated that further detailed investigations into the inflammatory process and kidney function post FURS is needed, as recent evidence links prolonged inflammation to scaring, which in combination with oxidative stress, contributes to the pathogenesis of diabetes mellitus, hypertension and diabetic nephropathy [27]. Work by Uğuz S et al, (2016) explored the effect on ozone therapy in reducing lithotripsy induced renal injury on rats during SWL and found that administering ozone resulted in significant changes to biochemical results, notably a reduction is AST and ALP, as well as ameliorating nitro-oxide stress [28]. Therefore, future monitoring for sustained inflammation combined with the potential for therapeutic intervention such as ozone therapy may lead to better patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Overall it can be appreciated that further detailed investigations into the inflammatory process and kidney function post FURS is needed, as recent evidence links prolonged inflammation to scaring, which in combination with oxidative stress, contributes to the pathogenesis of diabetes mellitus, hypertension and diabetic nephropathy [27]. Work by Uğuz S et al, (2016) explored the effect on ozone therapy in reducing lithotripsy induced renal injury on rats during SWL and found that administering ozone resulted in significant changes to biochemical results, notably a reduction is AST and ALP, as well as ameliorating nitro-oxide stress [28]. Therefore, future monitoring for sustained inflammation combined with the potential for therapeutic intervention such as ozone therapy may lead to better patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, adverse effects such as hematuria might be present after the procedure [ 98 ]. Experimentally, O 3 treatment has been proven as effective against the morphological and oxidative damage caused by shock wave therapy [ 99 ]. The novel therapy, due to its antimicrobial capacity, has also ameliorated oxidative damage caused by microorganisms in kidney infection (pyelonephritis) [ 88 ] and septic shock in kidneys [ 100 ], as well as in other organs [ 101 ].…”
Section: Damage Models and O 3 Effectmentioning
confidence: 99%